National Park Management in Indonesia: The Use of Ecosystem Services to Support Its Financial Needs - Syohih, Ubaidillah; Kojima, Motoko; Supriyono, Bambang; Wike, Wike (Jurnal Ilmiah Administrasi Publik, 2018)
The growing trends in the conservation forest management opens up opportunities for the use of ecosystem services. Indonesia has 54 national parks that can be utilized for generating incomes as well as conserving the biodiversity to eliminate the financial gap of national park management. To support the financial needs of national park management, the Government of Indonesia needs to regulate the potential ecosystem services, improve the service delivery to the stakeholders, and consider new ecosystem services in addition to invite new investors and/or new grants and implement the economic instruments of environment.